EVALUASI KINERJA SIMPANG TAK BERSINYAL (Studi kasus: Simpang Tiga Jambu Jl.Raya Duri Kosambi) - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
The increasing human need for motorized vehicles has an impact on the number of trips made by humans using motor vehicles will increase. This condition is seen during peak hours, namely during working hours and returning to work so that research is needed to reduce congestion and accidents that occur. Calculation of performance intersection use MKJI 1997. File of this research that got from survey in two times on one day, those are morning and afternoon. The results of the intersection research for the existing conditions produce a degree of saturation (DS) of 1.07. This value exceeds the limit suggested by MKJI 1997 for unsigned intersections (DS <0.75). some alternatives are used to improve the performance of the intersection. Alternative I is an unsignalized intersection by giving a traffic signal and produces DS = 0.92. Alternative II with geometric widening of road and traffic signal generating value DS = 0.74 and delay 32.16 det / smp. Level of intersection service is at level C which means stable traffic, travel speed and freedom of movement has been influenced by the large volume of traffic so that the driver can no longer choose the desired speed.